Assessment of flip angle–TR equivalence for standardized dissolved‐phase imaging of the lung with hyperpolarized 129Xe MRI. Issue 3 (22nd October 2018) - Ruppert, Kai; Amzajerdian, Faraz; Hamedani, Hooman; Xin, Yi; Loza, Luis; Achekzai, Tahmina; Duncan, Ian F.; Profka, Harrilla; Siddiqui, Sarmad; Pourfathi, Mehrdad; Sertic, Federico; Cereda, Maurizio F.; et al.
Abstract : Purpose: To investigate the feasibility of describing the impact of any flip angle–TR combination on the resulting distribution of the hyperpolarized xenon‐129 (HXe) dissolved‐phase magnetization in the chest using a single virtual parameter, TR90°, equiv . Methods: HXe MRI scans with simultaneous gas‐ (GP) and dissolved‐phase (DP) excitation were performed using 2D projection scans in mechanically ventilated rabbits. Measurements with DP flip angles ranging from 6–90° and TRs ranging from 8.3–500 ms were conducted. DP maps based on acquisitions of similar radio frequency pulse‐induced relaxation rates were compared. Results: The observed distribution of the DP magnetization was strongly affected by acquisition flip angle and TR. However, for flip angles up to 60°, measurements with the same radio frequency pulse‐induced relaxation rates, resulted in very similar DP images despite the presence of significant macroscopic gas transport processes. For flip angles approaching 90°, the downstream signal component decreased noticeably relative to acquisitions with lower flip angles. Nevertheless, the total DP signal continued to follow an empirically verified conversion equation over the entire investigated parameter range, which yields the equivalent TR of a hypothetical 90° measurement for any experimental flip angle–TR combination. Conclusion: We have introduced a method for converting the flip angle and TR of a given HXe DP measurement to a standardized metric based on the virtual quantity, TR90°, equiv, using their equivalent RF relaxation rates. This conversion permits the comparison of measurements obtained with different pulse sequence types or by different research groups using various acquisition parameters.